2008
DOI: 10.1073/pnas.0805565105
|View full text |Cite
|
Sign up to set email alerts
|

Increased survival of western corn rootworm on transgenic corn within three generations of on-plant greenhouse selection

Abstract: To delay evolution of insect resistance to transgenic crops producing Bacillus thuringiensis (Bt) toxins, nearby ''refuges'' of host plants not producing Bt toxins are required in many regions. Such refuges are expected to be most effective in slowing resistance when the toxin concentration in Bt crops is high enough to kill all or nearly all insects heterozygous for resistance. However, Bt corn, Zea mays, introduced recently does not meet this ''high-dose'' criterion for control of western corn rootworm (WCR)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

15
300
1
1

Year Published

2009
2009
2021
2021

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 189 publications
(317 citation statements)
references
References 28 publications
(24 reference statements)
15
300
1
1
Order By: Relevance
“…three generations, and previous studies found that Cry3Bb1-resistant populations in the field were associated with as few as three generations of selection (13,14,27). Thus, much of the Cry3 resistance found here likely either developed independently, or at least increased in magnitude, in each field.…”
Section: Discussionmentioning
confidence: 70%
See 1 more Smart Citation
“…three generations, and previous studies found that Cry3Bb1-resistant populations in the field were associated with as few as three generations of selection (13,14,27). Thus, much of the Cry3 resistance found here likely either developed independently, or at least increased in magnitude, in each field.…”
Section: Discussionmentioning
confidence: 70%
“…In contrast, Cry1Ac cotton targeting the pink bollworm does achieve a high dose (28), and the resistance ratio for on-plant survival of resistant pink bollworm on Cry1Ac cotton was >99 (Table S2). Similarly, resistance ratios for diet-based bioassays with Bt toxin were 22 for western corn rootworm with resistance to Cry3Bb1 maize and 520-1,700 for pink bollworm with resistance to Cry1Ac cotton (27,29). Thus, it appears that pest resistance to Bt crops that are not high dose may be characterized by resistance that (i) is less than the level of resistance necessary to injure high-dose crops and (ii) can evolve rapidly, in as few as three pest generations (13).…”
Section: Discussionmentioning
confidence: 99%
“…To attempt to predict the likely mechanism of resistance to Bt it has been routine practice to select the pest of interest with Bt in the laboratory. Laboratory-based selection invariably results in some level of resistance or increased tolerance; for example, the western corn rootworm has been able to develop laboratory-based resistance to all forms of Bt toxin with which it has been selected (Meihls et al 2008(Meihls et al , 2011. While the use of large starting populations from the field has increased the relevance of these types of Bt selection experiments because common, pre-existing Bt resistance alleles are included (Gould et al 1997), it is still not clear that laboratory selection can predict exactly what mechanisms of Bt resistance will appear in the field.…”
Section: Laboratory Vs Field Selectionmentioning
confidence: 99%
“…For the western corn rootworm, widespread Þeld-evolved resistance to Bt maize is a potential threat, given this insectÕs history of rapid adaptation to numerous management practices, including crop rotation and some conventional insecticides (Meinke et al 1998, Wright et al 2000, Levine et al 2002. In addition, evidence from recent studies suggests a lack of substantial Þt-ness costs of resistance (Oswald et al 2011, Meihls et al 2012, PetzoldÐMaxwell et al 2012a, and nonrecessive inheritance of resistance (Meihls et al 2008, PetzoldÐMaxwell et al 2012a, both of which increase the risk of resistance evolution. Thus, sustainable insect resistance management (IRM) strategies are essential for prolonging the effectiveness of Bt maize for management of western corn rootworm.…”
mentioning
confidence: 99%